2007
DOI: 10.1158/1535-7163.mct-07-0160
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-like domains required for glucose regulatory protein 58–mediated reductive activation of mitomycin C leading to DNA cross-linking

Abstract: Glucose regulatory protein (GRP58) is known to mediate mitomycin C (MMC) -induced DNA cross-linking. However, the mechanism remains elusive. We hypothesized that thioredoxin-like domains, one at NH 2 terminus and another at COOH terminus, are required for GRP58-mediated MMC reductive activation leading to DNA cross-linking. Site-directed mutagenesis mutated cysteines in thioredoxin domains to serines. Wild-type (WT) and mutant GRP58 were cloned in pcDNA to produce GRP58 V5-tagged WT and mutant proteins on tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…It has been shown earlier that mutations in thioredoxin like domains have no effect on subcellular localization of GRP58 [8]. There is very little information available on phosphorylation of GRP58 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown earlier that mutations in thioredoxin like domains have no effect on subcellular localization of GRP58 [8]. There is very little information available on phosphorylation of GRP58 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of GRP58 in mouse is lethal; however B cell specific deletion of GRP58 leads to impaired assembly of the major histocompatibility complex [3]. Besides, GRP58 is shown to play a role in gamete fusion [4], regulation of transcription factors like Ref1 [5], entry of SV40 in host cells [6] and in mitomycin C-induced DNA cross-linking [7–8]. …”
mentioning
confidence: 99%
“…It has been reported that MMC induces cytotoxicity via DNA cross‐linking and breaking ( 3,14 ) and GRP58 mediates MMC‐induced DNA cross‐linking. ( 12,14 ) In this study, we demonstrated that GRP58‐mediated cytotoxcity of MMC that led to DNA cross‐linking was inhibited by the combination treatment (Fig. 3).…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have revealed that a glucose regulatory protein (GRP58) requires thioredoxin-like domains to catalyze metabolic reduction of MMC to 2,7- diaminomitosene, which then cross-links DNA. [30,47] Therefore, in contrast to performing a detoxification role, dithiols could generate cytotoxic metabolites by reducing MMC in close proximity to the nucleus. [43] The proposed mechanism of reduction of MMC by dithiols should help elucidate the specific interactions of analogous biomolecules with MMC.…”
Section: Mode Of Actionmentioning
confidence: 99%